Redox-sensitive targeted nanoparticles synthesized from heparin mimetics for potential glioma treatment application - Yang Yang; Jie Zhang; Yuanpin Min; Wendi Zhou; Guozhong Lv (Carbohydrate Polymer Technologies and Applications)
Glioblastoma (GBM) is a highly aggressive primary brain tumor with a median survival of less than 15 months following standard treatments, largely due to obstacles such as the blood–brain barrier (BBB) and tumor heterogeneity. To overcome these challenges, we developed a redox-sensitive, targeted nanocarrier loaded with temozolomide (KCA-A2/TMZ), composed of K5 polysaccharide (derived from Escherichia coli fermentation), γ-linolenic acid, and the tumor-targeting peptide Angiopep-2 (A2). In vitro studies showed that KCA-A2 displayed excellent biocompatibility with NIH 3T3 (mouse embryonic fibroblasts) and bEnd.3 (mouse brain microvascular endothelial cells), maintaining over 90 % cell viability at 1 mg/mL. In contrast, it significantly inhibited the proliferation of C6 glioma cells (rat glioma) and HUVECs (human umbilical vein endothelial cells), indicating antitumor and anti-angiogenic properties. KCA-A2/TMZ further enhanced tumor cell inhibition, with an IC₅₀ of 250 μg/mL (containing 70 μg/mL TMZ) against C6 cells, more than 3-fold lower than that of free TMZ. Furthermore, a BBB in vitro model and confocal microscopy confirmed efficient brain-targeting capabilities. These findings suggest that the KCA-A2/TMZ system not only facilitates targeted TMZ delivery but also synergizes with the drug to inhibit GBM progression, offering a promising therapeutic strategy for improved glioblastoma treatment.